Discovery and characterization of a novel pathogen Erwinia pyri sp. nov. associated with pear dieback: taxonomic insights and genomic analysis - He, Linxin; Huang, Rong; Chen, Haiyan; Zhao, Liang; Zhang, Zhenfen (Frontiers in Microbiology, 2024)
In 2022, a novel disease similar to pear fire blight was found in a pear orchard in Zhangye City, Gansu Province, China. The disease mainly damages the branches, leaves, and fruits of the plant. To identify the pathogen, tissue isolation and pathogenicity testing (inoculating the potential pathogen on healthy plant tissues) were conducted. Furthermore, a comprehensive analysis encompassing the pathogen’s morphological, physiological, and biochemical characteristics and whole-genome sequencing was conducted. The results showed that among the eight isolates, the symptoms on the detached leaves and fruits inoculated with isolate DE2 were identical to those observed in the field. Verifying Koch’s postulates confirmed that DE2 was the pathogenic bacterium that causes the disease. Based on a 16S rRNA phylogenetic tree, isolate DE2 belongs to the genus Erwinia. Biolog and API 20E results also indicated that isolate DE2 is an undescribed species of Erwinia. Isolate DE2 was negative for oxidase. Subsequently, the complete genome sequence of isolate DE2 was determined and compared to the complete genome sequences of 29 other Erwinia species based on digital DNA–DNA hybridization (dDDH) and average nucleotide identity (ANI) analyses. The ANI and dDDH values between strain DE2 and Erwinia species were both below the species thresholds (ANI < 95–96%, dDDH<70%), suggesting that isolate DE2 is a new species of Erwinia. We will temporarily name strain DE2 as Erwinia pyri sp. nov. There were 548 predicted virulence factors in the genome of strain DE2, comprising 534 on the chromosome and 5 in the plasmids. The whole genome sequence of strain DE2 has been submitted to the NCBI database (ASM3075845v1) with accession number GCA_030758455.1. The strain DE2 has been preserved at the China Center for Type Culture Collection (CCTCC) under the deposit number CCTCC AB 2024080. This study represents the initial report of a potentially new bacterial species in the genus Erwinia that causes a novel pear dieback disease. The findings provide a valuable strain resource for the study of the genus Erwinia and establish a robust theoretical foundation for the prevention and control of emerging pear dieback diseases.